Vatnajökull Mass Loss Under Solar Geoengineering Due to the North Atlantic Meridional Overturning Circulation - Yue, Chao; Schmidt, Louise Steffensen; Zhao, Liyun; Wolovick, Michael; Moore, John C. (Earth's Future, 2021)
The objective of solar geoengineering by stratospheric aerosol injection (SAI) is to lower global temperatures, but it may also have adverse side effects. Iceland is situated close to the overturning regions of the Atlantic Meridional Overturning Circulation (AMOC) that warms the North Atlantic area. Hence, this may be one region where reduced irradiance by SAI may not be successful in reducing impacts from greenhouse gas warming. We examine this proposition by estimating how the Icelandic Vatnajökull ice cap (VIC) surface mass balance (SMB) and surface runoff changes in response to greenhouse gas and solar geoengineering scenarios over the period 1982–2089. We use the surface energy and mass balance model SEMIC driven by Earth System Model output under the GeoMIP G4, and CMIP RCP4.5 and RCP8.5 greenhouse gas scenarios. Geoengineering significantly reduces VIC near-surface air temperature by 0.4°C, downward longwave radiation by 2.4 Wm−2 and increases snowfall by 4.9 mm yr−1 relative to RCP4.5. During the SAI period 2020–2069, modeled annual mean SMB under G4, RCP4.5 and RCP8.5 are −0.34 ± 0.18 m yr−1, −0.56 ± 0.06 m yr−1 and −0.66 ± 0.04 m yr−1, respectively; surface runoff reduction under G4 is 6 ± 6% and 7 ± 6% (95% confidence interval uncertainties) compared with that under RCP4.5 and RCP8.5, which is far smaller than the 20 ± 2% and 32 ± 2% reductions for the Greenland ice sheet. The differences may be attributed to the reinvigoration of AMOC under G4 relative to RCP4.5 which brings more heat to Iceland than Greenland, leading to around half the cooling and longwave radiation reductions than for Greenland.